A critical analysis of the participation of the University of Cape Town community in the advancement of open scholarship: towards a strategy for the promotion of open scholarship - Nyahodza, Lena (Library and Information Studies Centre (LISC), 2023)
Open scholarship (OS) plays a significant role in improving access to knowledge as it removes cost barriers and copyright restrictions related to published research. As part of the openness movement, OS, particularly open access (OA), emerged in scholarly communication to bring radical change in scientific publishing through making publicly funded research immediately available to the reader at no cost. The University of Cape Town (UCT) has embraced the openness philosophy through establishing OA and research data management policies and has declared in its mission statement the desire to share its resources, including research to support development on the African continent. The objective of this study was to critically analyse UCT community's participation in the advancement of open scholarship to develop a strategy for the promotion of OS. The study was informed by the transformative worldview and adopted two theories, critical theory and the capability approach (CA) framework. It used a convergent transformative mixed method approach and a case study design to explore the case of OS at UCT. Both quantitative and qualitative data were collected using an online questionnaire completed by 207 academics and researchers; interviews with 10 representatives of faculty research committees, with volunteer researchers from faculties and with six key informants; focus group and individual discussions with 30 Masters students, PhD students and post-doctoral fellows; and, through content analysis of 17 documents. Quantitative data were analysed using both Excel and Strata while qualitative data were analysed using NVivo. The study found low uptake across the three open scholarship components (open research, open educational resources and open data) that were covered in this study. There was evidence that UCT academics and researchers view open scholarship as critical in supporting human development and social justice, and that they are motivated by social justice imperatives to engage in open scholarship practices. The study found that while there was the provision of OS infrastructure by UCT, funding for article processing charges (APCs) (albeit inadequate), established OA and open data policies, academic promotion at UCT, however, aligns research impact assessment with traditional bibliometrics indicators such as high impact factor of journals, which influence researchers to embrace a closed publishing culture. Lack of inclusion of open scholarship achievements in promotion criteria and inadequate APCs funding have been identified as major contributing factors in academics and researchers' low participation in OS as a social good. Critical theory was useful for engaging a scholarly communication study within a dominant capitalist society characterised by the commodification of knowledge; and this was evident in this study as the cost barrier has become a hinderance in publishing and in accessing knowledge as some of UCT's knowledge was found behind paywalls. A capability approach framework guided academics and researchers to identify strategies they have adopted to participate in OS and to identify elements they regarded as essential for the development of a strategy to support open scholarship including infrastructure, funding and organisational support. Based on academics and researchers' views of essential elements to support open scholarship and what worked for academics and researchers at UCT, this study proposed a strategy to support OS that could be used as a pilot by universities with similar experiences to those of UCT. The study recommends motivation of researchers to participate more in green OA through the incentivising of green OA practice for universities that have funding challenges to support gold OA. It also recommends prioritisation of accredited African-based diamond and gold OA access journals and collaboration to raise funds to support gold OA. The challenges experienced by UCT academics and researchers may be common among their peers in Africa and other global south regions, and hence the study recommends piloting, with adjustments as required, of the proposed strategy for purposes of advancing open scholarship. This could ground African researchers at the forefront of research production in Africa, as the continent is still grappling with inequalities of apartheid and colonialism and therefore require access to knowledge to support human development.